Temperature and humidity data acquisition design based on microcontroller ATMEGA8 - Sirajuddin Abbas; Samsul Hidayat; Nugroho Adi Pramono (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
The need for fast and accurate information is urgently needed to support human performance in various areas, including in the field of meteorology. Information about the weather parameters such as temperature and relative humidity on certain areas need to know quickly and accurately. For example the recording of temperature and humidity of a city, the mountains, or in disaster areas, it will definitely be easier if can be recorded automatically and continuously in a certain time. Therefore it needs a tool that can find out the weather parameters such as temperature and relative humidity on a certain position continuously and automatically. In this case the system can use data acquisition and data logger. System design used in this study consisted of DHT11 temperature and humidity sensor with digital output that is already terkalibrasi, microcontroller ATmega8 as the data processor of the DHT11 and the results will be displayed in the LCD. the display on the LCD always updated every 3 seconds. The results showed that "Temperature And Humidity Data Acquisition Design Based On Microcontroller ATmega8" Media has successfully created according to the specifications of the tool are expected.